2023
DOI: 10.3390/vetsci10020141
|View full text |Cite
|
Sign up to set email alerts
|

The Surveillance of Borrelia Species in Camelus dromedarius and Associated Ticks: The First Detection of Borrelia miyamotoi in Egypt

Abstract: Tick-borne diseases (TBDs) are emerging and re-emerging infections that have a worldwide impact on human and animal health. Lyme borreliosis (LB) is a severe zoonotic disease caused by the spirochete Borrelia burgdorferi sensu lato (s.l.) transmitted to humans by the bite of infected Ixodes ticks. Borrelia miyamotoi is a spirochete that causes relapsing fever (RF) and is genetically related to Borrelia burgdorferi s.l. However, there have been no reports of B. miyamotoi in Egypt, and the data on LB in camels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 61 publications
1
11
0
3
Order By: Relevance
“…Nevertheless, there have been no reported human B. miyamotoi infections in Egypt. Most recently, in Egypt, B. miyamotoi was rst identi ed in 6.8% of the camel blood samples using the glpQ gene(Ashour, et al, 2023). These results support our ndings of detection of 6% of rodents' blood was PCR positive to Borrelia miyamotoi.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, there have been no reported human B. miyamotoi infections in Egypt. Most recently, in Egypt, B. miyamotoi was rst identi ed in 6.8% of the camel blood samples using the glpQ gene(Ashour, et al, 2023). These results support our ndings of detection of 6% of rodents' blood was PCR positive to Borrelia miyamotoi.…”
supporting
confidence: 87%
“…They proposed that deer may possess a mechanism that prevents them from being infective to ticks. Few studies have detected B. burgdorferi in camel's blood(Ben Said et al, 2016 andAshour et al, 2023), and the potential role of camel in pathogen transmission and prediction of disease risk is still unknown. B. miyamotoi has been isolated from Ixodes persulcatus, and the rst case of B. miyamotoi infection in a human was discovered in Russia in 2011(Platonov et al, 2011).…”
mentioning
confidence: 99%
“…The main vectors of B. miyamotoi differ in different countries, such as I. scapularis and I. pacificus in the United States, I. ricinus in Europe, I. persulcatus , I. ovatus, H. concinna and H. longicornis in China, I. persulcatus and I. pavlovski in Japan, I. ricinus and I. persulcatus in Russia [ 6 ]. An increasing number of B. miyamotoi strains in ixodid ticks have been identified in many countries including the Czech Republic, Egypt, and Austria [ [21] , [22] , [23] ]. Here, our study showed that R. microplus , I. ovatus , H. nepalensis and H. kolonini may be novel vectors of relapsing fever spirochetes in Yunnan province.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three years, an increasing number of B. miyamotoi in ixodid ticks has been identified in many countries including the Czech Republic, Egypt, and Austria [ [21] , [22] , [23] ]. There has also been an increase in human infections in France, Austria, and Inner Mongolia Autonomous Region of China [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…Borrelia garinii belongs to the genus Borrelia and is responsible for causing Lyme disease [ 1 , 2 ]. It is the most common tick-borne disease in the Northern Hemisphere, with over 300,000 new cases reported each year in the United States alone [ 3 ].…”
Section: Introductionmentioning
confidence: 99%